Development of Public-Private Partnership in the Field of Educational Services - Duzelbayeva, Gulshat; Abdimomynova, Almakul; Baimahanova, Akmaral; Mukhtarova, Akmaral; Karbozova, Akzhan (European Scientific Journal, ESJ, 2018)
Public-private partnership in the field of education is a special form of cooperation between the state and business. It is built on the unification of resources that are available at their disposal. These resources are primarily intellectual resources and it entails the use of mutual advantages. Its goal is to provide socially significant services with mutual additional benefits on the basis of pre-calculated risks. This is due to the understanding that the effective implementation of the Stateâ€™s socio-economic programs depends, inter alia, on the level of development of business structures, which practically implements the priorities formed by the state. Nevertheless, Kazakhstan’s small business is not always able to develop independently in the context of demand by the modern conditions of the national economy.